2011
DOI: 10.1177/0891241611399437
|View full text |Cite
|
Sign up to set email alerts
|

Scrapbooking: Family Capital and the Construction of Family Discourse

Abstract: Through everyday activities, often performed by women, a version of family becomes reified for its members. Family discourse, linked to cultural capital via family capital, creates credentials and competence (family capital) in a particular family type and also a set of dispositions (family habitus) that inclines family members to act in ways consistent with normative standards of family. This article presents a holistic-content narrative analysis of one family’s eleven-volume scrapbook collection that reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…The industry, however, promotes the albums as for future generations, which is in line with LDS beliefs regarding researching and keeping family histories and suggests a less voluntary side of the hobby. This standard permeates the industry and is observed by other scholars (see Goodsell and Seiter 2011). My research indicates that among a heterogeneous sample, scrapbookers are less committed to this standard.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The industry, however, promotes the albums as for future generations, which is in line with LDS beliefs regarding researching and keeping family histories and suggests a less voluntary side of the hobby. This standard permeates the industry and is observed by other scholars (see Goodsell and Seiter 2011). My research indicates that among a heterogeneous sample, scrapbookers are less committed to this standard.…”
Section: Discussionsupporting
confidence: 58%
“…Women have historically played a primary role in maintaining family histories (i.e., kin work) (see di Leonardo ) and women have long dominated scrapbooking as hobbyists and industry workers. Earlier research on the hobby supported this finding and relied on samples of mostly white married mothers who scrapbook (see Demos ; Downs ; Goodsell and Seiter ; Stalp and Winge ). However, my experience as an industry worker challenged this perspective as I had interactions with memory keepers that were men; gay, lesbian, or bisexual; and of color.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…The importance of seeing families as historical and multigenerational is echoed by the life course perspective (Elder, ), particularly the concept of linked lives, and scholars have begun exploring the role of narrative in families (e.g., Gardner & Poole, ; Kellas, ; Langellier & Peterson, ; Pratt & Fiese, ; Smith, ; Weingarten, ). For example, Goodsell and Seiter () told how a mother constructed a narrative through a scrapbook, intended to convey to her children the knowledge, skills, and credentials associated with what she believed were the proper ways to do family. A narrative analysis of the scrapbook collection showed that she constructed (both literally and figuratively) family to be normative American middle class in terms of roles, rituals, and materials, while also allowing for agency on the part of individual family members.…”
Section: Aristotelianism and Family Researchmentioning
confidence: 99%